Skills required by bachelor nursing students to meet the challenges of digitalisation in healthcare – results of qualitative expert interviews - Palmdorf, Sarah; Behler, Annika; Ilskens, Karina; Büker, Christa; Latteck, Änne-Dörte (GMS Journal for Medical Education, 2025)
Objective: Through the digital transformation the everyday working life of nursing staff and the demands made on them are steadily changing. To meet these demands, Bachelor students need to learn appropriate “digital” skills during their courses. This study aimed at developing a module that imparts these digital skills. It was not clear which concrete skills the students should acquire and which topics should therefore be dealt with in the module. Methods: 24 semi-structured guide-based interviews with experts were carried out and analyzed with qualitative content analysis. The experts came from the field of science, technology manufacturing, practical applications/practitioners and pedagogics. Results: We identified 4 different areas of skills: (1) organizing successful collaboration with patients, relatives and other professionals (doctors, therapists, IT); (2) supporting patients and relatives in the use of assistive technologies; (3) planning and implementing projects related to assistive technologies (4) managing lifelong learning in relation to assistive technologies. A reflective use of digital technologies in patient care and the education of patients and relatives were described as key qualifications. Conclusions: On the basis of the different assessments of the experts, it was possible to identify and discuss a wide range of digital skills. This can be used to define learning objectives for appropriate modules or to evaluate existing ones. The study therefore contributes to evidence-based teaching.